Red pilled : the allure of digital hate - Munn, Luke (BiUP General, 2023)
Hate is being reinvented. Over the last two decades, online platforms have been used to repackage racist, sexist and xenophobic ideologies into new sociotechnical forms. Digital hate is ancient but novel, deploying the Internet to boost its allure and broaden its appeal. To understand the logic of hate, Luke Munn investigates four objects: 8chan, the cesspool of the Internet, QAnon, the popular meta-conspiracy, Parler, a social media site, and Gab, the »platform for the people.« Drawing together powerful human stories with insights from media studies, psychology, political science, and race and cultural studies, he portrays how digital hate infiltrates hearts and minds.
Keywords: vihapuhe; digitalisaatio; sosiaalinen media; salaliittoteoriat; viha